2019
DOI: 10.1016/j.bpsc.2018.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Individual-Level Approach to Identify Cortical Connectivity Biomarkers in Obsessive-Compulsive Disorder

Abstract: Our findings would seem to encourage the use of individual-level approaches to connectivity analyses to better delineate the cortical and subcortical networks underlying symptom severity and improvement at the dimensional level in OCD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 75 publications
(106 reference statements)
0
39
0
Order By: Relevance
“…Moreover, accurate qualification of between-network connectivity based on individualized ROIs will have particularly strong implications for clinical research, as recent studies have suggested that changes in between-network connectivity may signify normal brain development [63] as well as pathological changes [64]. The analytical framework developed in this study can be conveniently extended to the investigations of brain-behavior associations in clinical populations [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, accurate qualification of between-network connectivity based on individualized ROIs will have particularly strong implications for clinical research, as recent studies have suggested that changes in between-network connectivity may signify normal brain development [63] as well as pathological changes [64]. The analytical framework developed in this study can be conveniently extended to the investigations of brain-behavior associations in clinical populations [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…However, an individual-specific approach is critical in identifying biomarker and there is still need for implementing studies that detect functional brain circuit connections that track changes in global and dimension-specific symptom severity longitudinally, in the same patient. Recently, one study conducted in OCD patients [97] found that changes in connectivity pre-post treatment in the individual patient can predict YBOCS improvement, while connectivity was less predictive in template-based comparisons.…”
Section: Towards a Neurobiologically Based Approachmentioning
confidence: 99%
“…For the past few years, researchers have attempted to develop analytical methods that overcome such limitations, and machine-learning analyses have been one of those methods 31 , 32 . Owing to its advantages, few recent OCD studies have applied machine-learning algorithms with rsFC 17 , 33 , 34 . However, these studies have one or more of the following limitations: a relatively small sample size, involvement of medicated OCD patients in the analyses, or the absence of therapeutic response information.…”
Section: Introductionmentioning
confidence: 99%